Halangan dan Peluang Merevitalisasi Tradisi Tanam Padi Gaga di Desa Bali Kuna di Bali Utara - I Putu Mardika; I Gusti Agung Ngurah Agung Yudha Pramiswara (Universitas Udayana, 2022)
The ancient Balinese people of North Bali have a tradition of cultivating rice on dry soil, which is called ngaga. The people of Pedawa Village, one of the cluster of five ancient villages in Banjar sub-district, Buleleng Regency, have revitalized this agrarian culture that had been lost for nearly half a century. This study analyses the livelihood of the ngaga tradition in Pedawa Village following of its new development in the last three years. The study focuses on the causes for the reviving of the tradition, as well as the challenges and opportunities that it presents. The study concluded that the reason for the reviving this tradition was due to the need for rituals at Pucaksari Temple. Meanwhile, the obstacle is mostly because of the economic value of the gaga rice This article provides a practical contribution to the process of growing gaga rice in dry land, a cultural practice that the local community of Pedawa in North Bali had been forgotten.